Selje Spa Thalasso - en helse- og velværekatedral? - Bjelland, Anne Karen (Tidsskrift for kulturforskning, 2006)
The use of water in healing and curing has existed from the age of antiquity. Both water from mineral springs and ocean water have been used in many cultures around the world. During the last few years, a wave of spa treatments has swept over us, also in Norway. Hotel spa is a spa located within a hotel environment that provides guests with a variety of health and healing services, and gives opportunities for health enhancement and lifestyle improvement, stress reduction, well-being and relaxation. Thalassic therapy is healing by using ocean water and the beneficial qualities of a marine environment. The treatments are presented as both preventive and curing. This article examines some aspects of Selje Spa Thalasso, the only thalassic centre in Scandinavia. The centre is located by the Stadt Sea, at the edge of Selje beach in a "unique sacred landscape". I am presenting some of the thalassic treatments offered and categories of guests who are supposed to be typical. The centre is based on a holistic view of health, characterized by "The good circle", ideas that also exist within the alternative health movement. The article is also offering some reflections on Selje Spa Thalasso as a cathedral of health and well-being. At last some comments are related to the spa-wave in a Norwegian contemporary cultural and health policy context.